Suggestions for improving clinical utility of future guidelines for diagnosis and management of idiopathic pulmonary fibrosis: results of a Delphi survey - Funke-Chambour, Manuela; Albera, Carlo; Bendstrup, Elisabeth; Costabel, Ulrich; Grutters, Jan C.; Harari, Sergio; Johannson, Kerri A.; Kreuter, Michael; Strambu, Irina; Vancheri, Carlo; Varone, Francesco; Vitulo, Patrizio; et al. (The European respiratory journal, 2021)
Tweetable abstract ERSpublications - click to tweetEvidence-based guideline development is challenging. Implementation can be suboptimal. A Delphi survey among clinical experts evaluated possibilities to improve clinical utility and implementation of IPF and other ILD guidelines. http://bit.ly/3avcOug